The Factors Influencing the Risk Based Internal Audit in Improving the Effectiveness of Internal Audit - Taufik Kurniawan; Rina Br Bukit; Keulana Erwin (Universitas Pendidikan Ganesha, 2023)
Internal Control System (SPI) weaknesses hamper government performance; Therefore, the concept of Risk-Based Internal Audit (RBIA) through risk determination techniques based on priority scales is thought to be able to improve the effectiveness of internal control in North Sumatra Province. The purpose of this study is to determine the impact of Professional Development, Top Management Commitment, and the Role of Internal Audit on Risk-Based Internal Audit (RBIA), as well as its impact on the Effectiveness of Internal Audit both directly and indirectly in North Company. Sumatra Provincial Inspectorate. This study took quantitative methods. The population of this study is the Functional Position of Internal Auditor and Local Government Affairs Supervisor (PPUPD) which amounts to 101 people, while the informant is a party who understands the implementation of RBIA, namely Auxiliary Inspectors. The sampling technique used is census, meaning that the entire population is sampled in the study. The test used a variant-based Structural Equation Modeling (SEM) model with the Partial Least Squares (PLS) technique. Professional Development, Top Management Commitment, and the Role of Internal Audit are variables that allegedly affect the success of RBIA implementation in improving Internal Audit Effectiveness. The results showed that Professional Development, Top Management Commitment, and the Role of Internal Audit had a significant positive effect on the successful implementation of risk management with the RBIA method. The implication of these findings is the importance of the role of Professional Development, Top Management Commitment, and the Role of Internal Audit in improving the effectiveness of internal control within local government.